The importance of arterial ligations for the treatment of intracranial aneurysms - Avman, Nurhan (The Turkish Journal of Pediatrics, 1961)
A plastic model of the cerebral arterial tree was made and the hemodynamic changes were studied after certain occlusions. Because of technical difficulties, clinical workers have not been able to investigate these changes in man satisfactorily. The results have been given and their clinical significance has been discussed.